2020
DOI: 10.1371/journal.pone.0231730
|View full text |Cite
|
Sign up to set email alerts
|

Calculating air volume fractions from computed tomography images for chronic obstructive pulmonary disease diagnosis

Abstract: Quantitative evaluation using image biomarkers calculated from threshold-segmented lowattenuation areas on chest computed tomography (CT) images for diagnosing chronic obstructive pulmonary diseases (COPD) has been widely investigated. However, the segmentation results depend on the applied threshold and slice thickness of the CT images because of the partial volume effect (PVE). In this study, the air volume fraction (AV/TV) of lungs was calculated from CT images using a two-compartment model (TCM) for COPD d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Since the pathologic evaluation during the disease course of COVID-19 has not been established, computed tomography (CT) can reveal ground glass opacity and consolidation, which may reflect pathologic changes in these patients. Estimation of the volumetric quantification of chest CT images has been used in patients with various lung diseases including asthma, chronic obstructive pulmonary disease, interstitial lung disease, and oncological disease ( 9 10 11 ). Several studies have shown a potential role of chest CT volumetric quantification in predicting the mortality of ARDS ( 12 13 14 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the pathologic evaluation during the disease course of COVID-19 has not been established, computed tomography (CT) can reveal ground glass opacity and consolidation, which may reflect pathologic changes in these patients. Estimation of the volumetric quantification of chest CT images has been used in patients with various lung diseases including asthma, chronic obstructive pulmonary disease, interstitial lung disease, and oncological disease ( 9 10 11 ). Several studies have shown a potential role of chest CT volumetric quantification in predicting the mortality of ARDS ( 12 13 14 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in reality, for air‐rich tissues such as lungs, their CT density values vary widely depending on air inspiratory and exhaustive phases 24 . The CT density value of the lung can be derived by considering the mixture of lung parenchyma and air in a voxel; 27 in the inspiratory phase, the proportion of air in the lung increases and the CT density value becomes lower, while in the exhaust phase, it becomes higher. Therefore, if the CT density value of air changes due to the pixel value truncation, the CT density value of lung parenchyma can be anticipated to be impacted even if the noise does not reach 100 HU.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle and blood can be used as the representative tissue. The ROIs for muscle and blood can be specifically defined around or between ribs and in the aorta or ventricle, respectively 79. Air fraction obtained by this method is a dimensionless parameter, representing the air content (range, 0 to 1).…”
Section: Recent Qct Methodsmentioning
confidence: 99%
“…Therefore, air fraction is expected to be less sensitive to differences in scanners as compared with density-based methods. Air factions of 90% and 98.5% are set as thresholds for defining AT and emphysema, respectively 13,79. Furthermore, considering the fraction threshold for AT and the subject-specific HU of air and tissue, we can simply obtain a subject-specific threshold to define AT regions.…”
Section: Recent Qct Methodsmentioning
confidence: 99%
See 1 more Smart Citation